Tra drammaturgia e linguistica: analisi di "…tra la Carne e il Cielo" e intervista alla librettista Maddalena Mazzocut-Mis (Itinera, 2020)
...tra la Carne e il Cielo is an opera by Azio Corghi set to a libretto by Maddalena Mazzocut-Mis. The inspiration of the opera is the essay Studi sullo stile di Bach by Pier Paolo Pasolini, a critical analysis to Bach’s violin sonatas. Mazzocut-Mis re-uses Pasolini’s words in the libretto, while the music is a variation on Bach’s sonatas by Corghi. The aim of this paper is the analysis of the language of Pasolini and the dramaturgical use of his words in the opera focusing on the passage from essay to libretto.
Keywords: linguistics; dramaturgy; librettology; Pasolini; Bach.